Enantioselective Synthesis of Biaryl Compounds via Suzuki–Miyaura Cross-Coupling Using a Palladium Complex of 7′-Butoxy-7-(diphenylphosphino)-8,8′-biquinolyl: Investigation of a New Chiral Ligand Architecture - Wu, Zhenhua; Wang, Chao; Zakharov, Lev N.; Blakemore, Paul R. (Synthesis, 2014)
7,7′-Dihydroxy-8,8′-biquinolyl was converted to the title phosphine in four-steps via Mitsunobu monoetherification, trifylation, phosphination, and phosphine oxide reduction (63% overall yield). Enantiomerically pure phosphine was combined with Pd2dba3 and investigated for the synthesis of axially chiral biaryl compounds from Ar1Br and Ar2B(OH)2 in the presence of K3PO4 in toluene solvent (6 examples, 4–97% yield, 4–74% ee). The analogous carbocyclic ligand 2-(diphenylphosphino)-2′-methoxy-1,1′-binaphthyl (MOP) was studied for comparative purposes and found to be effective for the synthesis of hindered 2,2′-disubstituted 1,1′-binaphthyls (78–83% yield, 20–38% ee).
Keywords: asymmetric catalysis; atropisomerism; azaBINOL; cross-coupling; quinolines